2001
DOI: 10.1248/bpb.24.662
|View full text |Cite
|
Sign up to set email alerts
|

Stealth Polycyanoacrylate Nanoparticles as Tumor Necrosis Factor-.ALPHA. Carriers: Pharmacokinetics and Anti-tumor Effects.

Abstract: The objective of this study was to investigate the pharmacokinetics and in vivo anti-tumor effect of recombinant human tumor necrosis factor-a a (rHuTNF-a a) encapsulated in poly(methoxypolyethyleneglycol cyanoacrylate-co-n-hexadecyl cyanoacrylate) (PEG-PHDCA) nanoparticles. Our experimental results showed that PEG-PHDCA nanoparticles could extend the half-life of rHuTNF-a a to 7.42 h and obviously change the protein biodistribution in tissues, and in particular, increase accumulation of rHuTNF-a a in tumor. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…Surface modification of poly( n -butyl cyanoacrylate) nanoparticles with polysorbate 80 (a nonionic surfactant and emulsifier derived from polyethoxylated sorbitan oleate, commercially available under the trade name Tween 80) proved to cross the blood brain barrier in vivo [149]. Thanks to their high resistance and ability to deliver drugs to RES organs [150], other cyanoacrylic polymers such as poly( n -hexadecyl cyanoacrylate) [151] and poly(methoxypoly(ethylene glycol) cyanoacrylate- co - n -hexadecyl cyanoacrylate) [152,153,154,155] have been used for the preparation of nanoparticles.…”
Section: Nanocarriersmentioning
confidence: 99%
“…Surface modification of poly( n -butyl cyanoacrylate) nanoparticles with polysorbate 80 (a nonionic surfactant and emulsifier derived from polyethoxylated sorbitan oleate, commercially available under the trade name Tween 80) proved to cross the blood brain barrier in vivo [149]. Thanks to their high resistance and ability to deliver drugs to RES organs [150], other cyanoacrylic polymers such as poly( n -hexadecyl cyanoacrylate) [151] and poly(methoxypoly(ethylene glycol) cyanoacrylate- co - n -hexadecyl cyanoacrylate) [152,153,154,155] have been used for the preparation of nanoparticles.…”
Section: Nanocarriersmentioning
confidence: 99%
“…Stealth nanoparticles (NP) are characterized by a prolonged halflife in the blood compartment that allows them to extravasate and accumulate more in pathological sites, such as tumors with leaky vasculature caused by the "enhanced permeability and retention effect" [3,4] . In our previous study, higher intratumoral drug accumulation and antitumor potency were achieved for recombinant human tumor necrosis factor-alpha (rHuTNF-α)-loaded stealth poly (methoxypolyethyleneglycol cyanoacrylate-co-n-hexadecyl cyanoacrylate) (PEG-PHDCA) NP with sizes of approximately 150 nm and methoxypolyethyleneglycol (MePEG) molecular weight of 5000 [5] . It is known that surface properties, particle size, and drug release behavior are the key for the biological fate of stealth NP.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have also revealed that poly(methoxypolyethyleneglycol cyanoacrylate-co-n-hexadecylcyanoacrylate) NPs could enhance the half-life of TNF-α in tumor bearing mice along with the targeting efficiency and antitumor potency [60]. The increased antitumor activity might arise from the higher accumulation of nanotherapeutics in tumor tissues and longer plasma circulation time.…”
Section: Polymeric Nanocarriersmentioning
confidence: 99%